ANALISIS INOVASI PELAYANAN APLIKASIPENDAFTARAN TANPA ANTREAN DENGAN SISTEM ONLINE (PATHILO) DI RUMAH SAKIT UMUM DAERAH WONOSARI - Rona Patmasari; Retno Sunu Astuti, (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The era of globalization and modernity which implicates the intensification of mobility, information, technology, investment, resources, also affected people's mindsets that are increasingly critical in regard of the quality of public services. Community demands for excellent service encourage the government, as a service provider, to carry out various steps for continuous improvement to actualize better public services. One obvious effort to improve the quality of public services is to construct public services innovation. Efforts to improve service quality were also carried out by the Wonosari Regional Public Hospital through on The Application of Pendaftaran Tanpa Antrean dengan Sistem Online (Pathilo). Innovation analysis on Application Pathilo uses the innovation attribute theory proposed by Rogers and the theory of supporting factors and inhibitors from Clark and Albury. The result shows that the Pathilo Application contains relative advantages, compability, and triability albeit having complexity and observability that were not working well. The stimulus factors for the Pathilo Application innovation are political impulse, economic pressure, and enforcement for improved services while on the other hand there are also inhibiting factors which are over-dependent on high performers. Technology is apparent but hampered by cultural and organizational structuring, and there are no rewards or incentives. Management of information systems including the Pathilo Application server independently, intensive or rewards for employees involved in the Pathilo Application innovation, increased intensity of socialization, forthright and continuous introduction of Pathilo Application innovations to the community, and development of innovations and simplification of the Pathilo Application registration requirements are the proposition for a better innovation development on Pathilo.